The Participation of the Peoples of Dagestan in the Great Patriotic War - Vladimir Vladimirovich Gushch (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with the topic of participation of the peoples of the Caucasus in the Great Patriotic War. The analysis of the events that took place in the North Caucasus in 1942-1943. Highlighted the special role of the peoples of Dagestan in the fight against the Nazi invaders. Involved in such a complex topic as the collaboration.